2019
DOI: 10.18203/2394-6040.ijcmph20190613
|View full text |Cite
|
Sign up to set email alerts
|

An organization based cross-sectional study of occupational injuries among bridge construction workers in an urban area of Mumbai

Abstract: Background: Occupational injuries are matter of consideration and purport to be raising cost directly like in illnesses and accidents, loss of employment, disability and loss of productivity and subsequently to families and Society. However, there is paucity of studies to elucidate the state of affairs in most of the part of India. The Present study dictates the prevalence of injury and associated factors among Bridge Construction workers in urban area of Mumbai. Objectives are (1) to study prevalence of injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
2
3
2
Order By: Relevance
“…Around 65% of the workers were married in the current study, which is similar to the findings reported in studies conducted in Mumbai 6 where 58.9% workers were married and Kolkata 7 where 61% workers were married. This is in contrast to the findings of a study conducted by Daljeet kaur et al 8 loss of employment, disability and loss of productivity and subsequently to families and Society. However, there is paucity of studies to elucidate the state of affairs in most of the part of India.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Around 65% of the workers were married in the current study, which is similar to the findings reported in studies conducted in Mumbai 6 where 58.9% workers were married and Kolkata 7 where 61% workers were married. This is in contrast to the findings of a study conducted by Daljeet kaur et al 8 loss of employment, disability and loss of productivity and subsequently to families and Society. However, there is paucity of studies to elucidate the state of affairs in most of the part of India.…”
Section: Discussioncontrasting
confidence: 99%
“…Workers usually work for longer time to earn more wages and to meet the basic needs of life. Although the result is in contrast to the observation made by Daljeet Kaur et al 8 loss of employment, disability and loss of productivity and subsequently to families and Society. However, there is paucity of studies to elucidate the state of affairs in most of the part of India.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Occupational injuries pose major public health and developmental problems; which result in serious health, social, and economic consequences on workers and their employers [5]. Employees must understand when is necessary to use, what equipment is required, how to use or wear, how to care, how to know when the equipment has reached the end of its useful life and how to dispose of PPE [6,16,17]. The prevalence of occupational injury is high which is by low PPE usage [18].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors were not using protective devices, smoking, tobacco chewing, lack of sleep and work experience associated with suffering. 10 Further, forty-four percent of the industrial workers were affected by external injuries during their working time. 11 Twenty-one percent of the welders suffered from work-related injuries.…”
Section: Discussionmentioning
confidence: 99%